2012
DOI: 10.1007/s10886-012-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Male-Produced Pheromone in the European Woodwasp, Sirex noctilio

Abstract: A male-produced pheromone that attracts both males and females was identified for the European woodwasp, Sirex noctilio, a serious pest of pine trees. Males displayed excitatory behaviors when placed in groups, and were attracted to the odors from males that were 2-5-d-old, but not to odors from males that were 0-1-d-old. An unsaturated short-chain alcohol, (Z)-3-decen-1-ol, was discovered in samples collected on SuperQ filters over groups of males and identified by using micro-derivatization reactions and gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 26 publications
6
60
0
Order By: Relevance
“…Because S. noctilio has become an important invasive pest in a number of countries, efforts to identify attractants have been made using electrophysiology, field studies and laboratory bioassays (Simpson, ; Simpson & McQuilkin, ; Cooperband et al , ; Crook et al , ). Bashford () conducted field studies in Tasmania aimed at developing a trap and lure for S. noctilio to detect new populations without the use of trap trees, ground surveys or aerial surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Because S. noctilio has become an important invasive pest in a number of countries, efforts to identify attractants have been made using electrophysiology, field studies and laboratory bioassays (Simpson, ; Simpson & McQuilkin, ; Cooperband et al , ; Crook et al , ). Bashford () conducted field studies in Tasmania aimed at developing a trap and lure for S. noctilio to detect new populations without the use of trap trees, ground surveys or aerial surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Johnson et al (2013) found that intercept traps baited with semiochemicals (e.g., Sirex lure ϩ ipsenol ϩ ipsdienol) generally caught more S. nigricornis than trap trees. Semiochemicals are important for attracting S. noctilio as well (Bö rö czky et al 2009Cooperband et al 2012), but an effective combination and quantity of attractants has yet to be found. Future investigations should focus on developing and testing an effective attractant for S. noctilio.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have tested and improved lures for woodwasps (Siricidae) , Cooperband et al 2012, Coyle et al 2012, Johnson et al 2013, Barnes et al 2014), but information on effective trap type is limited to studies of related species (McIntosh et al 2001, Costello et al 2008, Barnes et al 2014. This is probably not because efforts have been lacking, but more likely because of difÞculty in comparing low S. noctilio catch among different traps.…”
mentioning
confidence: 99%
“…This approach has led to the identification of three contact sex pheromone components, (Z)-7-heptacosene, (Z)-7-nonacosene, and (Z)-9-nonacosene (Böröczky et al 2009). There is currently little evidence that the European woodwasp uses long-range sex pheromone communication, although Cooperband et al (2012) identified a potential male-produced pheromone candidate, but no field trapping data are available. This compound, (3Z)-decen-1-ol, may, in fact, be a volatile male-produced lek signalling pheromone (Thompson et al 2013).…”
Section: The European Woodwaspmentioning
confidence: 99%